Understanding how older people with mild frailty engage with behaviour change to support their independence: a qualitative study - Benjamin Gardner; Louise Marston; Kate R Walters; Vari M Drennan; Rachael Frost; Paul Chadwick; Rebecca L Gould; Yolanda Barrado-Martin; Sarah Gibson; Rekha Elaswarapu; Rashmi Kumar; Kalpa Kharicha; et al. (BMJ Open)
Objectives To explore barriers and facilitators to behaviour change in older people with mild frailty.Design Qualitative study.Setting Community-dwelling older people living with mild frailty.Participants 64 older people with mild frailty, workers delivering the service and stakeholders.Methods Semistructured interviews were conducted between July 2022 and May 2023 with participants in a randomised controlled trial (‘HomeHealth’) of a 6-month, home-based, personalised goal setting intervention, based around the Capability-Opportunity-Motivation-Behaviour model. We purposively sampled older participants receiving the service (n=49), workers delivering it (n=7) and stakeholders supporting its delivery (n=8). Interviews explored participation experiences, including engagement, perceived progress and impact. Transcripts were analysed using thematic analysis.Results Key themes included frailty symptoms and adapting/compensating for these, self-efficacy and beliefs about capacity or need for change, familiarity with goal-setting processes and health-related knowledge, accessibility of services and outdoor environments, and enabling social support. Participants were empowered to change behaviours with support, where personalised meaningful goals were set. These were maintained where they led to a tangible outcome and had increased self-efficacy; however, new health challenges and lack of intrinsic motivation could be barriers.Conclusions Regular and continued empathic person-centred support helps empower mildly frail people who are motivated to change their behaviour. Identifying those willing and able to identify their need for change may be key to maximise service use impact.Trial registration number ISRCTN54268283.